(untitled) (Fiep Bulletin - online, 2016)
The media has been a contradictory element when it comes to physical activity, especially on children, youth and adolescents in school age. This study aimed to observe the phases of the development of children are being affected and the degree of physical exercise is not consistent with age. The research was conducted with 41 students from 9 to 16 years, of both genders, attending the 6th to 9th grade of a School of Basic Education, the city of Joinville - SC and had as a research tool using a questionnaire and consequently the information obtained were compared to readings in articles and specialized books. With this study promoted the use of media as a way of learning for school, directing them to correct media use, imposing usage limits and primarily valuing physical activity and contact with other children, making the practice exercises becomes commonplace and synonymous with wellbeing. The media has been a contradictory element when it comes to physical activity, especially on children, youth and adolescents in school age. This study aimed to observe the phases of the development of children are being affected and the degree of physical exercise is not consistent with age. The research was conducted with 41 students from 9 to 16 years, of both genders, attending the 6th to 9th grade of a School of Basic Education, the city of Joinville - SC and had as a research tool using a questionnaire and consequently the information obtained were compared to readings in articles and specialized books. With this study promoted the use of media as a way of learning for school, directing them to correct media use, imposing usage limits and primarily valuing physical activity and contact with other children, making the practice exercises becomes commonplace and synonymous with wellbeing.